EFEKTIVITAS METODE EDUKASI GIZI DALAM MENINGKATKAN PENGETAHUAN GIZI IBU HAMIL: SYSTEMATIC LITERATURE REVIEW - Nuraliah Nuraliah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
A Nutrition knowledge in pregnant women is essential for healthy dietary decision-making. Low nutrition knowledge prevalence remains high in developing countries. To compare the effectiveness of various nutrition education methods in improving nutrition knowledge among pregnant women. Systematic literature review using PubMed, Scopus, Web of Science, and Google Scholar databases (2015-2025). Ten RCT/cluster-RCT articles on pregnant women receiving nutrition education met PRISMA inclusion criteria. Three main methods identified: (1) Health Belief Model-based counseling showed highest effectiveness with hemoglobin increase of 0.45 g/dL and anemia reduction from 14.7% to 9.2%; (2) mobile health interventions showed promising results with >80% compliance; (3) local food-based education resulted in 6.9-fold dietary diversity improvement. Minimum 12-week duration and 4-6 session frequency showed higher effectiveness. Combination of face-to-face counseling with digital media adapted to population characteristics provides optimal results.